Molecular detection of Mycobacterium ulcerans in the environment and its relationship with Buruli ulcer occurrence in Zio and Yoto districts of maritime region in Togo - Maman, Issaka; Tchacondo, Tchadjobo; Kere, Abiba Banla; Beissner, Marcus; Badziklou, Kossi; Tedihou, Ekanao; Nyaku, Edith; Amekuse, Komi; Wiedemann, Franz Xaver; Karou, Damintoti Simplice; Bretzel, Gisela (PLOS Neglected Tropical Diseases, 2018)
Author summary Buruli ulcer is a skin disease caused by Mycobacterium ulcerans. Although residence near aquatic areas has been identified as an important source of increased risk of contracting Buruli ulcer, the reservoir and the mode of transmission are not well known. To improve the understanding of the mode of transmission of M. ulcerans in human, we report here the first study of detection of M. ulcerans in the environment and its relationship with BU occurrence in Togo. This study confirms the presence of M. ulcerans DNA in the environment of Zio and Yoto districts of the maritime region. This study provides information on some possible reservoirs of the bacterium such as water, plants/biofilms and soil. Also, in this article we showed that the rivers of Haho and Zio could be potential sources of infection of M. ulcerans in human. Finally, data obtained from this study could explain partially the high rate of Buruli ulcer cases in these two districts of the maritime region in south Togo.